2013
DOI: 10.1016/j.molcel.2013.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Tandem Stem-Loops in roX RNAs Act Together to Mediate X Chromosome Dosage Compensation in Drosophila

Abstract: Summary Dosage compensation in Drosophila is an epigenetic phenomenon utilizing proteins and long noncoding RNAs (lncRNAs) for transcriptional upregulation of the male X chromosome. Here, by using UV crosslinking followed by deep sequencing, we show that two enzymes in the Male-Specific Lethal complex, MLE RNA helicase and MSL2 ubiquitin ligase, bind evolutionarily conserved domains containing tandem stem loops in roX1 and roX2 RNAs in vivo. These domains constitute the minimal RNA unit present in multiple cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
201
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 149 publications
(212 citation statements)
references
References 44 publications
7
201
0
Order By: Relevance
“…1E; Supplemental Fig. S1A,B), which is consistent with our previous report and shows that the new method is indeed comparable with iCLIP (Ilik et al 2013). Second, in the relative absence of roX1 RNA in S2 cells (Johansson et al 2011), we also observed several mRNAs that were bound by MLE at their introns and some that were bound at their 3 ′ untranslated regions (UTRs; 145 peaks are located on introns of 58 genes, and 72 peaks are located on 3 ′ UTRs of 13 genes).…”
Section: Uvclap Provides An Efficient Methods To Capture Rna-protein Isupporting
confidence: 92%
See 2 more Smart Citations
“…1E; Supplemental Fig. S1A,B), which is consistent with our previous report and shows that the new method is indeed comparable with iCLIP (Ilik et al 2013). Second, in the relative absence of roX1 RNA in S2 cells (Johansson et al 2011), we also observed several mRNAs that were bound by MLE at their introns and some that were bound at their 3 ′ untranslated regions (UTRs; 145 peaks are located on introns of 58 genes, and 72 peaks are located on 3 ′ UTRs of 13 genes).…”
Section: Uvclap Provides An Efficient Methods To Capture Rna-protein Isupporting
confidence: 92%
“…We showed previously that MLE has an unusually strong preference for two lncRNAs in Drosophila cells: roX1 and roX2 (Ilik et al 2013). Binding events on these two RNAs, as determined by iCLIP (individual nucleotide-resolution cross-linking and immunoprecipitation) (König et al 2010), comprise ∼80% of all binding events.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The minimal protein core complex lacking roX RNAs can still specifically acetylate histone H4 on lysine 16 within nucleosomes in vitro (Morales et al 2004), and overexpression of MSL proteins can partially overcome the lack of roX RNAs, suggesting that the proteins possess all of the essential functions of dosage compensation but require the RNAs to stimulate assembly and spreading (Oh et al 2003). Assembly of the complex is initiated when the secondary structure of the roX RNAs is modified, allowing the binding of MSL2 and providing the core for the full recruitment of the other MSL subunits (Ilik et al 2013;Maenner et al 2013). …”
Section: Noncoding Rox Rnas Facilitate Assembly and Targeting Of The mentioning
confidence: 99%
“…The RNA helicase MLE colocalizes with MSL2 at HAS and facilitates the incorporation of roX into the complex. The RNA is important for the distribution of the MSL-DCC along the X-chromosome, where it activates target genes 2,[5][6][7] .…”
mentioning
confidence: 99%